News sources and media bias - Armando J. Garcia-Pires; Hans Jarle Kind; Lars Sørgard (Center for Economic Studies and ifo Institute (CESifo), 2012)
In this paper we investigate the relationship between news sources and media firms. Although empirically important, this channel for supply-driven media bias has not previously been analyzed in economics literature. We model the relationship as an informal contract based on trust and punishment, where a news source decides if and how much information to provide to a media firm. Strategic interactions between these agents may have a significant impact on the level of media bias in the market. In particular, we show that in some cases the news source provides information if and only if there is competition in the media market, while in other cases competition between media firms reduces the amount of information that is made available to the audience.
Keywords: L14; L82; 330; news sources; media bias; informal contracts